Endometrial stromal sarcoma of uterus with metastasis to the lung and brain. (17th September 2012) - Akhavan, Ali; Shishebor, Forozan; Moghimi, Mansour; Binesh, Fariba
Abstract : Endometrial stromal sarcomas are rare tumours of the uterus and account for 10% of uterine sarcomas. Most of such tumours are low grade, although even these types can spread to the extrauterine areas; however, brain metastasis is very uncommon. This case report presents a 43-year-old Iranian woman with synchronous lung and brain metastases.